PERSEPSI DAN PERILAKU MASYARAKAT SEKITAR HUTAN MANGROVE TERHADAP PELESTARIAN MANGROVE DI KAWASAN TAMAN HUTAN RAYA NGURAH RAI BALI - Setiastri, Catarina Tenny; Windia, I Wayan; Astarini, Ida Ayu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 13 No 2 (2019)DO - 10.24843/EJES.2019.v13.i02.p02, 2019)
Ngurah Rai Forest Park Bali is a mangrove conservation which covers 1,373.50 ha; the largest mangrove forest area in Bali. However, its strategic location, in the center of business and the golden triangle of tourism (Sanur, Nusa Dua, and Kuta), creates pressures from various interests. This threat causes 253.40 ha of mangrove forest area in Ngurah Rai Forest Park Bali severely damaged. The aims of this study were: (1) to analyze the forms of land function change occurred in Ngurah Rai Forest Park Bali; (2) to analyze perception of the community around Ngurah Rai Forest Park Bali about mangrove conservation; (3) to analyze the behavior of the community around Ngurah Rai Forest Park Bali about mangrove conservation. The research was conducted from May until July 2018 in Tuban and Pedungan District. This study uses 2 (two) analytical methods, 1) literature study methods, to determine the form of land function change that occurred in the Ngurah Rai Area of ??Bali, 2) categorical quantitative analysis method to determine the perceptions and behavior of the local community. The categorical quantitative analysis method was used to categorize the perceptions and behaviors of local people. It is qualified into 4 (four) categories on a Likert scale. The results of the questionnaire collected were categorized into 4 (four) levels and discussed descriptively. This paper was based on primary data taken using questionnaire with a predetermined analysis unit to interview the community in the study area. The result presented with quantitative and descriptive analysis. The result shows that within twelve years, from 2000 to 2012, Ngurah Rai Forest Park Bali has a land function change of 29.76 ha or 2.16%; from 1,161.76 ha in 2000 to 1,132.00 ha in 2012. The level of community perception towards the mangrove preservation of Ngurah Rai Forest Park Bali is very good but the level of its community behavior is bad. It can concluded that good perception do not always have a good impact of people behavior towards the mangrove conservation.